An exploratory temporal analysis of the lodging market and state economic recovery from Hurricane Sandy (The lodging market recovery from Hurricane Sandy). Issue 5 (13th May 2019) - Choi, Danny Woosik; Lee, Seoki; Singal, Manisha
Abstract : Purpose: The purpose of this study is to examine how the lodging market and the state economy affected by Hurricane Sandy have recovered from the damages sustained. Specifically, this study examines and predicts the influence of revenue management key performance indicators (KPIs) on recovery and lodging revenue in the affected states and the states' economies. These KPIs include average daily rate (ADR), occupancy and revenue per available room (RevPAR). Design/methodology/approach: Secondary financial data were collected for the states most damaged by Hurricane Sandy. Subsequently, pooled Ordinary Least Square (OLS) regression was conducted combining time and non-time dependent variables based on the states and radius from the landfall. Findings: The results indicate that although the lodging market and the state economies have recovered since the onslaught of Hurricane Sandy, certain KPIs still need to improve. Practical implications: Managerial implications are suggested in terms of dynamic pricing, market-based recovery, the KPIs, federal aid and facility management. Originality/value: Despite its importance, research on the effects of climate change in the hospitality context has not actively progressed after Hurricane Katrina. Time and non-time dependent variables are combined in this analysis to gain a richer understanding of the impacts and recovery of KPIs on the revenue in the lodging market and the revenue on states' economies. Additional analysis based on the radius from the landfall of the hurricane was performed to examine the impact and recovery based on geographical proximity.